Effect of Anti-Base Erosion and Profit Shifting Rules on International Income-Shifting - Jorge Manuel Brás Pereira (2019)
Multinational groups have used instruments like intra-debt financing and transfer-mispricing to shift their profits by locating their subsidiaries in countries with lower corporate income tax rates. Many countries have introduced stricter legislation to reduce BEPS. The purpose of this investigation is to study whether stricter rules regarding transfer-pricing and interests' deductibility have been successful in battling international profit shifting. In order to develop our research, we use a sample of 21 018 foreign subsidiaries located in EU-28 and in Switzerland for the period 2008-2016. We then conduct a panel-data analysis with control for both cross-section and time fixed-effects. Our estimated results show that firms reallocate income in function of tax rate differences and that the implemented legislation led to a reduction of international income shifting. We also show that firms with higher shares of intangible assets can escape easier to tighter transfer-pricing rules. We contribute to a scarce but growing literature on a matter of great interest for international tax experts